Could Primary Tumor Resection Improve Survival in Metastatic Breast Cancer? (International Journal of Scientific Research and Management (IJSRM), 2021)
Introduction: In advanced breast cancer, local treatment is considered palliative. However, although there are some polemic opinions about the surgical treatment, some of the latest studies have emphasized that in advanced cases primary tumor resection (PTR) is related to better outcomes. This review aims to evaluate how resection of the original tumor impacts women with metastatic breast cancer, considering the most recent studies about this subject. Methods: The search was performed in MEDLINE, Scopus, PMC, Current Contents and Wiley Online Library databases; 23 articles - from 2016 to 2019 - were selected and 11 were included in this review. As inclusion criteria were considered: studies presenting outcomes about resection of the primary tumor, comparison between chemotherapy/ hormone therapy/ targeted cancer therapies and surgical intervention, studies published from 2016 to 2019 and available in English, Spanish or Portuguese. We excluded those which did not approach PTR, did not present outcomes of interest (progression-free survival comparison between PTR and systemic therapy) or only discussed systemic therapy, as well as those published before 2016. Results: It was reported in 6 studies that progression-free survival is better on those who underwent surgery. PTR was also related to longer median overall survival in women submitted to surgery, up to 16 months higher when compared to the ones who were not. Enhanced survival even pertained to surgical groups regardless of tumor size. Conclusion: Based in the analysis, PTR in metastatic breast cancer can be related to higher overall survival.